2000
DOI: 10.1054/jhsb.2000.0385
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of ADCON-T/N, a New Anti-Adhesion Barrier Gel, in Fresh Divisions of the Flexor Tendons in Zone II

Abstract: In a prospective randomized clinical trial, ADCON-T/N was investigated with regard to its effectiveness in fresh traumatic injuries of the flexor tendons in Zone II of the hand. Thirty patients participated in the trial. Following a standardized technique of tendon repair, the total active motion (TAM) and total extension lag (TEL) were determined after 12 weeks and evaluated according to the Buck-Gramcko score. Excellent results were achieved in 15 out of 16 patients in the ADCON-T/N group and 12 out of 14 in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 16 publications
0
19
0
Order By: Relevance
“…Merle et al [16] studied a bioresorbable gel composed of a carbohydrate polymer (ADCON-T/N). Although a decrease in tendon adhesion formation was demonstrated in an animal model, clinical trial results have been disappointing, and there is some question as to whether the material migrates from the repair site [17]. In our study, we also determined that normal walking analysis of the experimental side was better compared to the control side in which no adhesion barrier had been used after tendon repair surgery.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…Merle et al [16] studied a bioresorbable gel composed of a carbohydrate polymer (ADCON-T/N). Although a decrease in tendon adhesion formation was demonstrated in an animal model, clinical trial results have been disappointing, and there is some question as to whether the material migrates from the repair site [17]. In our study, we also determined that normal walking analysis of the experimental side was better compared to the control side in which no adhesion barrier had been used after tendon repair surgery.…”
Section: Discussionmentioning
confidence: 71%
“…In recent years, the focus has turned to diffusible membranes. Isik et al [17] used a hyaluronic acid membrane in a chicken model and showed adhesions were inhibited. This has not found wide clinical application, however, because the material is difficult to prepare and must be sewn around the tendon repair.…”
Section: Discussionmentioning
confidence: 99%
“…They are intended to prevent the formation of adhesions by wrapping or covering the tendons. Nevertheless, the results are controversial [14] and delayed wound healing has been reported [15,16]. And up to now, these products have only been used to prevent adhesions of flexor tendons at the wrist or finger [16][17][18].…”
Section: Discussionmentioning
confidence: 99%
“…ADCON-T/N, a bioresorbable gel composed of gelatine and a carbohydrate polymer in phosphate buffered saline, was shown to have no benefit in one trial [26], while advantage in post-surgical finger mobility was reported in the second clinical trial [27] in zone II flexor tendon repair. However, there was a risk for significant disadvantages as increased delayed rupture rate of the repaired tendon was reported in the ADCON group [28].…”
Section: Discussionmentioning
confidence: 99%